Analysis of Herbicides Residues of Farmland Soil Samples in Some Selected Villages from Pankshin Local Government Area, Plateau State, Nigeria - M Gudam, T.; A Shibdawa, M.; Y Chindo, I.; W Lungfa, C. (International Journal of Advanced Chemistry, 2021)
Most recently, there has been an increase in the use of herbicides to control weeds by farmers in Pankshin Local Government Area (LGA), Plateau State. The use of herbicides in farming activities has significantly provided more hope and assurance for sustainable food security in most countries of the world as bumper harvest have always been recorded.in its usage however the residues of the herbicides after successive accumulation by the years could be a threat to humans and other non-target organisms after they have performed their primary roles. From an interview with the farmers it was discovered that glyphosate, paraquat dichloride and 2,4-dichlorophenoxy acetic acid are mostly used within the study area which are hazardous and should be handled with utmost care. Soil samples were obtained from Bumnan, Bwarak, Larpya and control. The samples were pretreated and subjected to the following analysis: Extractions, crystallization and recrystallization with the aid of acetone, dichloromethane, hexane and methanol as solvents. Physicochemical properties of the soil samples were determined and the following range of results were obtained: pH 5.2-5.3, % organic matter 4.02-8.23, EC 10-50 ÂµS/cm, residual moisture 0.5-3.0% and CEC 16.52-29.63cmolKg-1. GC analysis was carried out on the crystals and extracts to determine the herbicides concentrations and the following results were obtained in mg/kg: Bumnan â€“ 0.005 and 0.026, Bwarak- 0.004 and 0.008, Larpya- 0.015 and 0.033 and control 0.002 and 0.007 concentrations of 4, 4- bipyridine and 2,4-diphynoxyacetic acid respectively.Â Â